Perioperative Protocol of Ankle Fracture and Distal Radius Fracture Based on Enhanced Recovery after Surgery Program: A Multicenter Prospective Clinical Controlled study. (7th June 2022) - Li, Ting; Sun, Zhi-Jian; Zhou, Yan; Sun, Wei-Tong; Wang, Peng-Cheng; Cai, Xin-Yu; Liang, Jun-Bo; Dong, Jing-Ming; Zhou, Da-Peng; Yu, Kai; Wu, Ming-Xin; He, Jiu-Sheng; et al.
Abstract : Background . The enhanced recovery after surgery (ERAS) program is aimed to shorten patients' recovery process and improve clinical outcomes. This study aimed to compare the outcomes between the ERAS program and the traditional pathway among patients with ankle fracture and distal radius fracture. Methods . This is a multicenter prospective clinical controlled study consisting of 323 consecutive adults with ankle fracture from 12 centers and 323 consecutive adults with distal radial fracture from 13 centers scheduled for open reduction and internal fixation between January 2017 and December 2018. According to the perioperative protocol, patients were divided into two groups: the ERAS group and the traditional group. The primary outcome was the patients' satisfaction of the whole treatment on discharge and at 6 months postoperatively. The secondary outcomes include delapsed time between admission and surgery, length of hospital stay, postoperative complications, functional score, and the MOS item short form health survey-36. Results . Data describing 772 patients with ankle fracture and 658 patients with distal radius fracture were collected, of which 323 patients with ankle fracture and 323 patients with distal radial fracture were included for analysis. The patients in the ERAS group showed higher satisfaction levels on discharge and at 6 months postoperatively than in the traditional group (P < 0.001 ). In the subgroup analysis, patients with distal radial fracture in the ERAS group were more satisfied with the treatment (P = 0.001 ). Furthermore, patients with ankle fracture had less time in bed (P < 0.001 ) and shorter hospital stay (P < 0.001 ) and patients with distal radial fracture received surgery quickly after being admitted into the ward in the ERAS group than in the traditional group (P = 0.001 ). Conclusions . Perioperative protocol based on the ERAS program was associated with high satisfaction levels, less time in bed, and short hospital stay without increased complication rate and decreased functional outcomes.